2000
DOI: 10.1038/sj.gene.6363683
|View full text |Cite
|
Sign up to set email alerts
|

Immuno- and genetic therapy in autoimmune diseases

Abstract: Animal models of autoimmune disease have been developed that mimic some aspects of the pathophysiology of human disease. These models have increased our understanding of possible mechanisms of pathogenesis at the molecular and cellular level and have been important in the testing, development and validation of new immunotherapies. The susceptibility to develop disease in the majority of these models is polygenic as is the case in humans. The exceptions to this rule are gene knock outs and transgenic models of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 140 publications
(153 reference statements)
0
3
0
Order By: Relevance
“…One of these, interleukin l p (IL-lp), is found in the circulation during immunoinflammatory conditions and is secreted in and around pancreatic islets of Langerhans in the early stages of type I diabetes. We and others have previously shown that low levels of IL-1 p inhibit glucose-stimulated insulin secretion by pancreatic islets and that high levels of the cytokine are uniquely toxic to pan-creatic p-cells (3)(4)(5)(6)(7)(8). The mechanism behind this is poorly understood (7,9), and increased knowledge of the spectrum of activities initiated by IL-1p in p-cells is a prerequisite for better understanding the susceptibility of p-cells to immunoinflammatory attacks and, hence, the molecular basis of type I diabetes.…”
mentioning
confidence: 99%
“…One of these, interleukin l p (IL-lp), is found in the circulation during immunoinflammatory conditions and is secreted in and around pancreatic islets of Langerhans in the early stages of type I diabetes. We and others have previously shown that low levels of IL-1 p inhibit glucose-stimulated insulin secretion by pancreatic islets and that high levels of the cytokine are uniquely toxic to pan-creatic p-cells (3)(4)(5)(6)(7)(8). The mechanism behind this is poorly understood (7,9), and increased knowledge of the spectrum of activities initiated by IL-1p in p-cells is a prerequisite for better understanding the susceptibility of p-cells to immunoinflammatory attacks and, hence, the molecular basis of type I diabetes.…”
mentioning
confidence: 99%
“…Evidence from animal models supports convincingly that gene therapy can be an advantageous strategy in the treatment of inflammatory autoimmune disorders [19,20,25–28]. Recent reports of gene therapy in EAE have studied the use of hybridoma cells and CNS antigen‐specific T cells to deliver IL‐4 or TGF‐ β [19,26].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, islet transplantation suffers from scarcity of donors, the need for long-term immunosuppression, and short-term survival of transplanted cells because of recurrence of anti-islet cell autoimmunity. 4,5 Therefore, engineering alternative routes of physiologic insulin delivery is a major goal of diabetes research.…”
Section: Introductionmentioning
confidence: 99%